The Nemourinae (Insecta, Nemouridae) of the eastern Nearctic - Grubbs, Scott A.; Baumann, Richard W. (Zootaxa, 2023)
Morphology-based concepts of the 26 eastern Nearctic species of the subfamily Nemourinae (Insecta, Nemouridae) Billberg, 1820 are reviewed. Nemourinae is represented in this region by Nemoura Latrielle, 1796, Ostrocerca Ricker, 1952, Paranemoura Needham & Claassen, 1925, Podmosta Ricker, 1952, Prostoia Ricker, 1952, Shipsa Ricker, 1952, Soyedina Ricker, 1952, and Zapada Ricker, 1952. Wing venation and patterns of mottling are depicted with standard light microscopy. Diagnostic external reproductive structures are emphasized with line drawings, scanning electron microscopy, and standard light microscopy. A genus-level key to male and female adults is included. Species-level keys for Ostrocerca, Paranemoura, Prostoia, Soyedina, and Zapada are also provided.